Body contouring and liposuction - Rubin, J. Peter (Elsevier Saunders, 2013)
From fat grafts and liposuction through total body lift following massive weight loss surgery, this title includes full-color photos and procedural videos that show you exactly how to proceed, step by step, and achieve gratifying results.